Core pathology of eating disorders as measured by the Eating Disorder Examination Questionnaire (EDE‐Q): the predictive role of a nested general (g) and primary factors. Issue 3 (19th August 2013) - Friborg, Oddgeir; Reas, Deborah L.; Rosenvinge, Jan H.; Rø, Øyvind
Abstract The present study examined several factor models of the Eating Disorder Examination Questionnaire (EDE‐Q), and in particular, whether a nested general factor ('g') was present, hence supporting a common pathology factor. A total of 1094 women were randomly selected by Statistics Norway and mailed a questionnaire packet. The sample was randomly split, using the first half for exploratory analyses and the second for confirmatory validation purposes. A four‐factor solution received the best support, but the structure deviated from the original model of Fairburn. The internal consistency was high for the first three factors (.93, .82 and .86) and satisfactory for the fourth (.78). The additional specification of a general (g) factor improved model fit significantly, implying that the EDE‐Q scores are indicators of both a general core and four primary symptom patterns. Furthermore, the g was more strongly related to predictors like age and body mass index (BMI) than the four primary factors in a full structural equation model. The validity of interpreting the global EDE‐Q score as indicative of g was supported. A brief Shape and Weight Concern subscale of 11 items was strongly related to the g‐factor, and may provide an abbreviated measure of overall eating disorder pathology. Copyright © 2013 John Wiley & Sons, Ltd.